The effect of Arnebia purpurea extract on the survival of random pattern skin flaps in rats - Orhan, Erkan; Yüzbaşıoğlu, Merve; Erol, Yağmur Reyyan; Bilensoy, Erem; Erdoğar, Nazlı; Demirezer, Lütfiye Ömür; Kuruüzüm-uz, Ayşe (The European Research Journal, 2018)
Objectives. One of the important causes of flap losses is ischemia-reperfusion damage. Arnebia species are rich in naphthoquinone derivatives which known to have anti-inflammatory and anti-oxidant effects. The aim of the present study was to investigate the effects of Arnebia purpurea extract on viability of the skin flaps.Methods. Eighteen Wistar rats were divided in three groups. Caudal-based 9×3 cm size skin flap were applied  on dorsum of the all rats and following surgery, 2 cc of A. purpurea extract topically was applied to the group 1 and 2 cc of 0.2% Nitrofurazon cream topically was applied to the group 2, daily. The Group 3 only received flap surgery (control group). Seven days later, all subjects were euthanatized and necrosis rate in their flaps was calculated and compared to each other. Results. The necrosis rate was calculated as 20.25% ± 1.59% in Group 1, 32.05% ± 2.23% in the Group 2 and 37.33% ± 4.12% in the Group 3. It was found that necrosis rate in the Group 1 was statistically significantly less than Groups 2 and 3 (p < 0.001) and that difference in necrosis rate between Group 2 and Group 3 was not statistically significant (p > 0.05). Conclusion. Necrosis of skin flaps was reduced through topical application of A. purpurea extract.